Does Voice Benefit or Harm Occupational Well‐Being? The Role of Job Insecurity. (25th January 2021) - Röllmann, Laura Frederike; Weiss, Mona; Zacher, Hannes
Abstract: Although employee voice is integral for organizational functioning, it is not well understood how voice affects occupational well‐being, particularly when jobs are perceived as insecure. Drawing from the dual‐pathway model of proactivity, which is based on self‐determination and conservation of resources theories, we integrate theorizing on the well‐being consequences of voice with the job insecurity literature. First, we hypothesize that voice leads to increases in both vigour and fatigue. Second, we propose that job insecurity moderates these effects, such that the effect of voice on increases in vigour is stronger (weaker) when job insecurity is low (high), whereas the effect of voice on increases in fatigue is stronger (weaker) when job insecurity is high (low). Seven hundred and thirty three full‐time employees in Germany participated in two surveys, three months apart. Results largely supported our predictions and showed that voice led to increases in vigour. Moreover, voice predicted increases (decreases) in fatigue when job insecurity was high (low). However, voice and job insecurity did not interact in predicting changes in vigour. Reverse causal analyses showed no effects of vigour and fatigue on changes in voice. Our discussion focuses on why and how perceptions of employment relations should be considered to determine well‐being consequences of voice.